A base-stabilized silylene-promoted C(sp³)-H borylation and H₂ activation - Khoo, Sabrina (2021)
Treatment of the amidinato amidosilylene [L{(Me3Si)2N}Si:] [1, L = PhC(NtBu)2] with a slight excess of borane-tetrahydrofuran complex [BH3·THF] in toluene at room temperature afforded the silylene-borane adduct [L{(Me3Si)2N}Si:→BH3] (2). A triflate substituent was introduced on the boron center by reacting 2 with methyl triflate [MeOTf] (OTf = OSO2CF3) in toluene at room temperature to form [L{(Me3Si)2N}Si:→BH2OTf] (3), with the elimination of CH4 gas. The intramolecular C(sp3)-H borylation and H2 elimination occurred by reacting complex 3 with 1 in refluxing toluene to form a C-B bond in the resulting silylene-boronium ion 5. Complex 5 activated H2 gas or NH3BH3 at room temperature to form silylene-borane adduct 2 and [L{(Me3Si)2N}Si-H]OTf. Additionally, the reaction of 5 with H2 was studied through density functional theory calculations.